FMDV Leader Protein Interacts with the NACHT and LRR Domains of NLRP3 to Promote IL-1β Production - Sk Mohiuddin Choudhury; Xusheng Ma; Yuanyuan Li; Xiaofeng Nian; Zhikuan Luo; Yonghua Ma; Zixiang Zhu; Fan Yang; Weijun Cao; Haixue Zheng (Viruses, 2021)
Foot-and-mouth disease virus (FMDV) infection causes inflammatory clinical symptoms, such as high fever and vesicular lesions, even death of animals. Interleukin-1β (IL-1β) is an inflammatory cytokine that plays an essential role in inflammatory responses against viral infection. The viruses have developed multiple strategies to induce the inflammatory responses, including regulation of IL-1β production. However, the molecular mechanism underlying the induction of IL-1β by FMDV remains not fully understood. Here, we found that FMDV robustly induced IL-1β production in macrophages and pigs. Infection of Casp-1 inhibitor-treated cells and NOD-, LRR- and pyrin domain-containing 3 (NLRP3)-knockdown cells indicated that NLRP3 is essential for FMDV-induced IL-1β secretion. More importantly, we found that FMDV Lpro associates with the NACHT and LRR domains of NLRP3 to promote NLRP3 inflammasome assembly and IL-1β secretion. Moreover, FMDV Lpro induces calcium influx and potassium efflux, which trigger NLRP3 activation. Our data revealed the mechanism underlying the activation of the NLRP3 inflammasome after FMDV Lpro expression, thus providing insights for the control of FMDV infection-induced inflammation.